Laypeople in law: moving from a blind spot in socio-legal studies towards a comprehensive field of research - Kretschmann, Andrea (Laypeople in law, 2024)
While laypeople hold an important role in law, socio-legal scholars mainly focus on legal professionals and their activities in legal institutions, including parliaments, courts, tribunals, and international organizations. In this chapter, it is argued that a more systematic approach to contemporary research on laypeople in law is needed. We propose a research agenda that first engages with the question of how to distinguish laypeople from legal experts and second approaches a systematic account of the extent to which laypeople indirectly or directly contribute to law-making, judicial interpretation, and shifting legal practice. Finally, such an agenda addresses the question of how laypeople themselves are shaped by their legal context, which is highly dependent on their social, political, and historical environment.